2014
DOI: 10.1080/19415257.2014.924985
|View full text |Cite
|
Sign up to set email alerts
|

Leading practice development: voices from the middle

Abstract: Leadership has long been acknowledged as a significant dimension in effective school functioning and, indeed, school leaders can play a substantial role in professional development of staff. Here we have centred on the practices of leading as opposed to the qualities or characteristics of leaders, and this is emphasised by our use of the term 'leading' rather than 'leadership'. In this article we explicitly focus on the leading practices of practitioners we describe as middle leaders, those with an acknowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
65
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 106 publications
(90 citation statements)
references
References 23 publications
2
65
0
7
Order By: Relevance
“…This provided me with feedback about the dangers of lumping together all ‘hard to reach parents’. I also became mindful of the structure provided by Mrs Magpie—creating ‘hospitable conditions’ that both enabled and in some ways, constrained, sometimes guided, the practices of her two early career teachers, now acting essentially as middle leaders (Grootenboer et al., , p. 518).…”
Section: Level 3: Organisational Support and Changementioning
confidence: 99%
“…This provided me with feedback about the dangers of lumping together all ‘hard to reach parents’. I also became mindful of the structure provided by Mrs Magpie—creating ‘hospitable conditions’ that both enabled and in some ways, constrained, sometimes guided, the practices of her two early career teachers, now acting essentially as middle leaders (Grootenboer et al., , p. 518).…”
Section: Level 3: Organisational Support and Changementioning
confidence: 99%
“…278), and that their leading is practised 'below' the positional head (e.g. principal) and simultaneously 'above' and 'among' the teaching staff (Grootenboer et al 2015a). The notion of acknowledgement is crucial for teachers engaged in development work, as for some middle leaders, their work is not always a paid position in the hierarchical structure of the school; but it is work acknowledged by their teacher peers.…”
Section: Leading In Educationmentioning
confidence: 99%
“…Teachers' involvement in action research also helps to generate practices of leadership on the part of these teachers (Edwards-Groves and Rönnerman, 2013) -often expressed in practices of facilitating peers during collective reflective practices. In recent studies, Grootenboer et al (2015) have identified how such middle leading practices, involving teachers leading their colleagues' pedagogical change, begin with critical reflections on their practices and require a capacity to enable teachers' voices and agency for developing their own practices.…”
Section: The Nature Of Action Research: Personal Professional and Pomentioning
confidence: 99%